Copper iodide nanoparticles as a hole transport layer to CdTe photovoltaics: 5.5 % efficient back-illuminated bifacial CdTe solar cells - Pokhrel, Dipendra; Bastola, Ebin; Khanal Subedi, Kamala; Rijal, Suman; Jamarkattel, Manoj K.; Awni, Rasha A.; Phillips, Adam B.; Yan, Yanfa; Heben, Michael J.; Ellingson, Randy J. (Solar energy materials and solar cells, 2022)
We report the role of copper iodide (CuI) nanoparticles (NPs) as a hole transport layer (HTL) in cadmium sulfide/cadmium telluride (CdS/CdTe) photovoltaics. These CuI NPs were prepared using solution processing at room temperature and used to fabricate monofacial and bifacial CdTe solar cells with different back contacts. Using CuI/Au as the back contact, the device efficiency reached to 14.8% with outstanding fill factor (FF) of 79.2%. Replacing the gold (Au) electrode with sputtered transparent indium tin oxide (ITO), a CuI/ITO back contact yielded photoconversion efficiencies (PCEs) of 11.6% and 5.5% under front and back illumination respectively. Bifacial devices (CdTe/ITO) without the CuI NP HTL have an efficiency of 7.0% and 1.0% for front and back illumination, respectively. For CuI/ITO, a current collection of 12.0 mAcm−2 was observed upon back illumination which significantly improved over an ITO-only back contact (5.0 mAcm−2). The PCE obtained from back illumination was enhanced when using CuI NPs as the HTL due to the reduced back barrier height, and improved back interface as determined by temperature dependent current vs. voltage characteristics and impedance spectroscopy analysis. The improvement in device performance of the bifacial configuration is a significant step forward toward realizing thin film photovoltaic modules which harvest energy incident on the rear of the module. [Display omitted] •Investigated CuI Nanoparticles (NPs) as Hole Transport Layer (HTL) for Monofacial and Bifacial CdS/CdTe devices.•CuI NPs helps to improve photo conversion efficiency by significant improvement in open-circuit voltage (Voc) and fill factor (FF) of the devices.•Bifacial devices with absorber layer thickness (3.3 μm) showed excellent short circuit current density (Jsc = 12.0 mAcm−2) with back illumination reaching the device efficiency of 5.5% (bifaciality of 0.47).